Neonatal colonization of germ-free mice with Bifidobacterium longum prevents allergic sensitization to major birch pollen allergen Bet v 1 - Schwarzer, Martin; Srutkova, Dagmar; Schabussova, Irma; Hudcovic, Tomas; Akgün, Johnnie; Wiedermann, Ursula; Kozakova, Hana (Vaccine, 2013)
The main goal in reversing the allergy epidemic is the development of effective prophylactic strategies. We investigated the prophylactic effect of neonatal mother-to-offspring mono-colonization with Bifidobacterium longum ssp. longum CCM 7952 on subsequent allergic sensitization. Adult male and female germ-free (GF) mice were mono-colonized with B. longum, mated and their offspring, as well as age-matched GF controls, were sensitized with the major birch pollen allergen Bet v 1. Furthermore, signaling pathways involved in the recognition of B. longum were investigated in vitro. Neonatal mono-colonization of GF mice with B. longum suppressed Bet v 1-specific IgE-dependent β-hexosaminidase release as well as levels of total IgE and allergen-specific IgG2a in serum compared to sensitized GF controls. Accordingly, Bet v 1-induced production of both Th1- and Th2-associated cytokines in spleen cell cultures was significantly reduced in these mice. The general suppression of Bet v 1-specific immune responses in B. longum-colonized mice was associated with increased levels of regulatory cytokines IL-10 and TGF-β in serum. In vitro, B. longum induced low maturation status of bone marrow-derived dendritic cells and production of IL-10 in TLR2-, MyD88-, and MAPK-dependent manner. Our data demonstrate that neonatal mono-colonization with B. longum reduces allergic sensitization, likely by activation of regulatory responses via TLR2, MyD88, and MAPK signaling pathways. Thus, B. longum might be a promising candidate for perinatal intervention strategies against the onset of allergic diseases in humans.
Keywords: gastrointestinální trakt; Immunoglobulin E; Mice, Inbred BALB C; Hypersensitivity; imunologická tolerance; alergie; cytokiny; Disease Models, Animal; Gastrointestinal Tract; mužské pohlaví; Bifidobacterium; hexosaminidasy; Mice; Cytokines; Allergy; gnotobiologické modely; Probiotics; modely nemocí na zvířatech; ženské pohlaví; Immunization; zvířata; Antigens, Plant; imunoglobulin E; TLR2; Germ-Free Life; myši inbrední BALB C; myši; Hexosaminidases; antigeny rostlinné; Immune Tolerance; Germ-free mice; imunizace; Female; Male; Animals